1993
DOI: 10.1002/nau.1930120303
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic biofeedback training for children with bladder‐sphincter dyscoordination during voiding

Abstract: Neurologically normal children with recurrent urinary tract infections (UTIs), night- and daytime wetting, and urge and painful voiding may have staccato voiding due to pelvic floor contractions. The immediate effect of non-invasive urodynamic biofeedback (BF) therapy was assessed using a historical follow-up study in 31 children aged 5-15 years suffering from urodynamically proven overactive urethra during voiding. A long-term follow-up study was performed to investigate whether improvement was maintained. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 19 publications
1
11
0
3
Order By: Relevance
“…22,23 More recently, biofeedback treatment directed toward teaching external urethral sphincter/pelvic floor relaxation during voiding using perineal, vaginal, or anal placed surface electrodes for electromyogram has been reported. 20,21 Kunin et al 24 reported the prevalence rate for recurrent urinary tract infections in children to be .04% in boys and 1.1% in girls in a community-wide survey of school children in Virginia. We observed a 3% rate for urinary tract infection in constipated boys and a 33% rate in constipated girls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…22,23 More recently, biofeedback treatment directed toward teaching external urethral sphincter/pelvic floor relaxation during voiding using perineal, vaginal, or anal placed surface electrodes for electromyogram has been reported. 20,21 Kunin et al 24 reported the prevalence rate for recurrent urinary tract infections in children to be .04% in boys and 1.1% in girls in a community-wide survey of school children in Virginia. We observed a 3% rate for urinary tract infection in constipated boys and a 33% rate in constipated girls.…”
Section: Discussionmentioning
confidence: 98%
“…4,5,16,20,21 The treatment of these children may include timed voiding, anticholinergics, and continuous administration of prophylactic antibiotics. 22,23 More recently, biofeedback treatment directed toward teaching external urethral sphincter/pelvic floor relaxation during voiding using perineal, vaginal, or anal placed surface electrodes for electromyogram has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…With a limited number of between 1 and 9 training sessions, half of 32 children achieved complete and a quarter achieved partial success, with coordinated micturitions and long-term stability (Kjolseth et al, 1993). Also, the daytime wetting often subsides 443 DAY AND NIGHT WETTING spontaneously (Olbing, 1993), while concomitant nighttime wetting can be treated effectively.…”
Section: Detrusor-sphincter-dyscoordinationmentioning
confidence: 99%
“…Detrusor-SphinkterDyskoordination [27] "Dysco-ordinated voiding" [12] "Bladder sphincter incoordination" [18] "Bladder-sphincter dyscoordination" [22] "Vesical sphincter dyssynergia" [23] "Idiopathic detrusor sphincter dyssynergia" Eine chronische Obstipation ist neben der Harninkontinenz eine weitere Indikation für das Biofeedbacktraining [2,31]. Ein Zusammenhang einer Dysfunktion von Blase und Darm ist bekannt, die Mechanismen sind aber bislang ungeklärt [33].…”
Section: Synonyme Für Die Detrusor-sphinkter-dyskoordination (Deutschunclassified
“…Während des Trainings sollten die Patienten, hier die Kinder mit Harninkontinenz, den physiologischen Prozess zu erfassen und unter regelmäßiger Kontrolle zu korrigieren lernen [22]. Ziel ist, in einem weiteren Schritt das Erlernte auch ohne kontinuierliche bewusste Kontrolle umsetzen zu können (⊡ Tabelle 3).…”
Section: Trainingsprogramme Und Ergebnisseunclassified